Inovasi Penilaian Pembelajaran Bahasa Arab: Penilaian Kinerja Pada Keterampilan Kalam Di MAN 3 Sleman - Rosyada, Amrina (Balai Diklat Keagamaan Surabaya, 2024)
This research was motivated because the evaluation of Arabic learning in MAN 3 Sleman did not include the maharah kalam aspect. The purpose of this study was to provide a performance appraisal test instrument for maharah kalam in class XI MAN 3 Sleman. The performance appraisal is in the form of guided dialogue practice with the theme السفر (Traveling). This research is included in descriptive qualitative research with field studies (field reasearch). The primary data source in this study is grade XI science 2 students at MAN 3 Sleman. Secondary data sources are DIY Arabic teaching modules, Arabic learning guides and assessment books. Data collection techniques use observation, documentation and document analysis techniques. The results of using the test instrument get quite good results, namely students who have the category 'very competent' with a percentage of 41%, students who have the category 'competent' with a percentage of 52% while students who have the category 'quite competent' with a percentage of 7%. This article contributes to provide references related to performance appraisal in maharah kalam in class XI.